2018
DOI: 10.14411/fp.2018.002
|View full text |Cite
|
Sign up to set email alerts
|

High density of fox and cat faeces in kitchen gardens and resulting rodent exposure to Echinococcus multilocularis and Toxoplasma gondii

Abstract: The faeces of the red fox, Vulpes vulpes (Linnaeus), and the domestic cat, Felis catus (Linnaeus), can be responsible for spreading eggs of Echinococcus multilocularis Leuckart, 1863 and oocysts of Toxoplasma gondii (Nicolle et Manceaux, 1908) into the environment. The accidental ingestion of these eggs or oocysts, through consumption of raw fruits or vegetables grown in or in contact with contaminated soil, can lead to alveolar echinococcosis (AE) or toxoplasmosis in humans. The present study provides a quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
(51 reference statements)
2
20
0
Order By: Relevance
“…Studies show that pets, dogs, and cats excrete infectious E. multilocularis eggs (6, 810). The case-control study from Tyrol, in which hunting poses a risk, also showed a connection between cats and AE in western Austria (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that pets, dogs, and cats excrete infectious E. multilocularis eggs (6, 810). The case-control study from Tyrol, in which hunting poses a risk, also showed a connection between cats and AE in western Austria (25).…”
Section: Discussionmentioning
confidence: 99%
“…The raccoon dog ( Nyctereutes procyonoides ) as neozoon species plays a similar role as the red fox as final host (4, 5). Also, pets, especially dogs, can also act as final hosts and contaminate the environment by excreting infective E. multilocularis eggs (610). Humans acquire the infection by peroral ingestion of E. multilocularis eggs present in contaminated soil, food, or animal skins (6, 11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a range of zoonotic parasites is transmitted to humans via environmental stages excreted in animal faeces. Intestinal zoonotic helminths and protozoa of free-roaming canids including domestic dogs and foxes as well as those from free-roaming domestic cats play a major role in contaminating the environment, including recreational areas, private kitchen gardens and agricultural areas, with resistant parasite stages [ 6 , 7 , 8 , 9 ]. Especially, the uncontrolled growth of stray dog populations in South America, Africa, large parts of Asia and Southern Europe represent an emerging “One Health” problem as a source of zoonoses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other studies focused on landscape-related exposures compared outcomes in various habitats but their designs were too different to form a group for synthesis: Bastien et al [94] explored the interface between wild and domestic definitive hosts (respectively foxes and cats) and tested the effect on human prevalence; Hegglin et al [95] compared infection in foxes in different types of habitats (urban, border, and peri-urban habitats); Robardet et al [96] also studied the infection in foxes along an urbanization gradient, in relation with intermediate host populations.…”
Section: Landscape-related Exposuresmentioning
confidence: 99%